Toxic Leadership and Turnover Intentions: The Role of Burnout Syndrome - Abiúd Nunes; Ana Palma-Moreira (Administrative Sciences, 2024)
This study aimed to test the effect of toxic leadership on turnover intentions and whether burnout syndrome mediates this relationship. This study’s sample consists of 309 participants who work in organizations based in Portugal and Angola. The results indicate that toxic leadership positively and significantly affects burnout syndrome and turnover intentions. As for burnout, only the disengagement dimension positively and significantly affects turnover intentions. Disengagement partially mediates the relationship between toxic leadership and turnover intentions for participants working in Portugal and a total mediation effect for participants working in Angola. Organizations should be concerned about the leadership style adopted by their leaders, because if there is a toxic leader, this will lead to burnout syndrome in their subordinates and cause them to leave the organization, since turnover intentions are the best predictor of voluntary departure from the organization.